Bile acid–farnesoid X receptor–fibroblast growth factor 19 axis in patients with short bowel syndrome: The randomized, glepaglutide phase 2 trial. Issue 4 (1st September 2021) - Hvistendahl, Mark Krogh; Naimi, Rahim Mohammad; Hansen, Svend Høime; Rehfeld, Jens Frederik; Kissow, Hannelouise; Pedersen, Jens; Dragsted, Lars Ove; Sonne, David Peick; Knop, Filip Krag; Jeppesen, Palle Bekker
Abstract: Background: The gut‐liver axis and enterohepatic circulation have gained increasing attention lately. Patients with short bowel syndrome (SBS) are, in fact, human knock‐out models that may assist in the understanding of bile acid synthesis and regulation. We evaluated effect of glepaglutide (a long‐acting glucagon‐like peptide‐2 analog) on bile acid synthesis (the enterohepatic circulation of bile acids and liver biochemistry in patients with SBS). Method: In a single‐center, double‐blinded, dose‐finding, crossover phase 2 trial, 18 patients with SBS were randomly assigned to 2 of 3 treatment arms (0.1, 1, and 10 mg) with daily subcutaneous injections of glepaglutide for 3 weeks. The washout period between the 2 treatment periods was 4–8 weeks. Measurements were performed at baseline and at the end of each treatment period and included postprandial plasma samples for fibroblast growth factor 19 (FGF19), 7α‐hydroxy‐4‐cholesten‐3‐one (C4), total excretion of fecal bile acids, gene expression of farnesoid X receptor (FXR) in intestinal mucosal biopsies, total plasma bile acids, and liver biochemistry. Results: Compared with baseline, the median (interquartile range) postprandial response (area under the curve 0–2h) of FGF19 increased by 150 h × ng/L (41, 195; P = 0.001) and C4 decreased by 82 h × µg/L (−169, −28; p = 0.010) in the 10‐mg dose. FXR gene expression did not change in any of the groups. Alkaline phosphatase significantly decreased. Conclusion: Glepaglutide may stimulate the bile acid/FXR/FGF19 axis, leading to increased plasma concentrations of FGF19. Thereby, glepaglutide may ameliorate the accelerated de novo bile acid synthesis and play a role in the prevention and/or treatment of intestinal failure–associated liver disease.